The inventive organization : hope and daring at work / Jill Janov. - Janov, Jill, 1942- (The Jossey-Bass management series., 1994)
"As the Late Industrial Era has given way to the Information Era, long-held assumptions about organizational effectiveness have become obsolete. Steep hierarchies are no longer needed to get things done. It is the quality of relationships - between producers and consumers, among work associates, and between individuals and the means by which they produce - that determines and sustains organizational success." "In The Inventive Organization, Jill Janov offers inspiration, frameworks, and practical applications for executives, managers, and organization consultants who are facing the fundamental challenges in organizations today: how to sustain success in a constantly changing global economy, how to redesign work processes for optimal effectiveness, and how to realign roles and relationships as flattened hierarchies necessitate self-regulation throughout the entire organization." "Drawing on her extensive consulting experience with such organizations as Johnson & Johnson, Xerox, Ford, and 3M Company, Jill Janov explores how these and other companies are making the transition to high-performance, inventive organizations where self-regulation, interdependence, and partnerships are the rule. Janov shows how any organization that hopes to thrive into the next century can learn to develop the essential building blocks to inventiveness: focus on customer needs, concentrate on core work, practice "living" organizational values, think systematically, promote self-regulation, build and support interdependence, and understand leading as guiding the development of the system and following as pursuing common cause."--BOOK JACKET.